Association Of Maternal Stressors During Pregnancy With Postpartum Depression (PPD), A Cross-Sectional Analytical Study : Maternal Stressors during Pregnancy - Bilal, Sana; Saeed, Imrana; Idrees, Tayyaba; Abbas, Farrukh; Mansoor, Maryam; Khan, Zainab Idrees (Journal of Rawalpindi Medical College, 2025)
Objective: Postpartum depression can negatively impact both the mother's health and the child's development if treatment is not received. This study's goals are to discover different prenatal stressors and ascertain if the mother's stress during pregnancy is linked to postpartum depression. Materials & Methods: Using a consecutive sampling technique, an analytical cross-sectional study was conducted at postnatal wards, EPI centers and Gynae OPD of women aged 20 to 45 during the postpartum period (one week to six months). The study excluded female participants having a history of chronic illness, psychiatric medication, or a diagnosis of psychiatric disorder. The Edinburgh Post-Depression Scale and self-structured pre-partum stressors were included in an interview-based questionnaire. Results: Of the 313 mothers, 63.3% experienced mild stress, 32.6% experienced moderate anxiety, and 3.8% experienced severe stress. Inflation (82%), husband issues (64%), abuse at the hands of the husband (55%), and housekeeping during pregnancy (52%), were the most frequent sources of stress. Postpartum depression was seven times more likely to occur in those with high stress levels. Conclusion: Prepartum stress was modest for the majority of participants. The main causes of stress were things like inflation, followed by problems with the spouse, abuse at the hands of the husband, concerns about the children's schooling, and the amount of chores that came with being pregnant. Postpartum depression was more common in those with high stress levels.